PERANCANGAN SISTEM INFORMASI PENANAMAN MODAL DI BADAN KOORDINASI PROMOSI DAN PENANAMAN MODAL DAERAH (BKPPMD) PROVINSI JAWA BARAT - Marliana Budhiningtias Winanti; Dimas Prayogo (Jurnal Manajemen Informatika (JAMIKA), 2012)
Coordination Agency for Promotion and Regional Investment (BKPPMD) Jawabarat Province at the current system has the problem of data processing and investment cooperation that is not properly organized. In this study aims to find out , make the design , testing and implementing the Capital Investment Information System at the Provincial BKPPMD Bandung. usefulness this study consisted of practical usefulness and usability of academic.The method used is descriptive method with approach of case BKPPMD Jawabarat Province. Systems Development Method used by writer is method Prototype. The software used in this study are Microsoft Windows XP Professional SP as OS / Operating System database server used is Microsoft's database server is SQL Server 2000 and Investors information system using Visual Basic 6.0 programming language.From the results of this study concluded that computerization and Reporting is required in the process of Investment, With this application program all data concerned with investment activity can be maintained, the effectiveness and efficiency can be achieved with a good time, With this application program which comes with a password, needs to improvecontrols and data security is guaranteed because not everyone has the right to access data or change data.